AKTIVITAS HARIAN OWA JAWA (Hylobates moloch) DI PUSAT REHABILITASI SATWA PRIMATA JAWA CIWIDEY JAWA BARAT - Reni Srimulyaningsih; Ramdan Permadi (Wanamukti: Jurnal Penelitian Kehutanan, 2022)
Owa jawa (Javan gibbon) is one of endemic primate of West Java that is vulnerable to extinction. In connection with the decline in the species population, conservation efforts need to be taken immediately, one of the supporting aspects is information about daily activities. The object of research is to identify the daily activities of javan gibbon in Javan Primate Rehabilitation Centre Ciwidey, West Java. The method of resesarch is recording of activities of each individual is carried out for seven days at intervals of 5 minutes. The result is javan gibbon daily activities in the Javan Primate Rehabilitation Center were 5945 times carried out by 3 javan gibbon individuals with eight observed activities, are eating, drinking, moving, grooming, urination, defecation, sound and rest, which began at 06.00 WIB and ended in the afternoon at 16.00 WIB. The number of daily activities from the highest to the lowest are 2596 times (43.66%) mobile activity, 2189 times (36.82%) resting activities, 593 meals (9.97%), 353 times grooming (5.93%), vote 95 times (1.59%), urinate 44 times (0.74%), drink 39 times (0.65%) and defecate 36 times (0.60%).